2020
DOI: 10.1101/2020.02.04.934356
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic Disruption of Serine Biosynthesis is a Key Driver of Macular Telangiectasia Type 2 Etiology and Progression

Abstract: PurposeMacular telangiectasia type 2 (MacTel) is a rare, heritable and largely untreatable retinal disorder, often comorbid with diabetes. Genetic risk loci subtend retinal vascular calibre, and glycine/serine/threonine metabolism genes. Serine deficiency may contribute to MacTel via neurotoxic deoxysphingolipid production, however, an independent vascular contribution is also suspected. Here we use statistical genetics to dissect the causal mechanisms underpinning this complex disease. MethodsWe integrated ge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Specifically, the most significant SNPs were located in the genes PSPH (rs6955423 in locus 7p11.2; P = 5.9 × 10 −09 ), TTC39B (rs677622, 9p22.3; P = 3.2 × 10 −09 ), and REEP3 (rs10995566, 10q21.3; P = 4.8 × 10 −08 ). A further two loci tagged by rs9820465 between the genes SLC4A7 and EOMES (3p24.1, P = 5.6 × 10 −09 ), and rs139412173 near CERS4 (19p13.2, P = 2.9 × 10 −08 ), were previously implicated in a GWAS of MacTel conditioned on genetically predicted glycine and serine 7 . We identified two novel GW-significant loci tagged by rs2160387 in locus 2p14 (P = 5.9 × 10 −09 ), located within the alanine/glycine/ serine transporter gene SLC1A4, and rs17279437 in locus 3p21.31 (P = 6.2 × 10 −10 ) within the glycine transporter gene SLC6A20.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the most significant SNPs were located in the genes PSPH (rs6955423 in locus 7p11.2; P = 5.9 × 10 −09 ), TTC39B (rs677622, 9p22.3; P = 3.2 × 10 −09 ), and REEP3 (rs10995566, 10q21.3; P = 4.8 × 10 −08 ). A further two loci tagged by rs9820465 between the genes SLC4A7 and EOMES (3p24.1, P = 5.6 × 10 −09 ), and rs139412173 near CERS4 (19p13.2, P = 2.9 × 10 −08 ), were previously implicated in a GWAS of MacTel conditioned on genetically predicted glycine and serine 7 . We identified two novel GW-significant loci tagged by rs2160387 in locus 2p14 (P = 5.9 × 10 −09 ), located within the alanine/glycine/ serine transporter gene SLC1A4, and rs17279437 in locus 3p21.31 (P = 6.2 × 10 −10 ) within the glycine transporter gene SLC6A20.…”
Section: Resultsmentioning
confidence: 99%
“…Mendelian randomisation. Using Mendelian randomisation analysis we recently demonstrated that low serine and glycine levels, as well as high alanine levels, were likely to have a causal effect on MacTel aetiology 7 . Applying Mendelian randomisation analysis to these new GWAS results we found that genetically predicted serum serine concentrations was again the strongest and most significantly associated trait among 141 predicted metabolites (Supplementary Data 15).…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Mac Tel 2 is currently considered to be a primary neurodegenerative condition of the retina with secondary vascular involvement rather than (as previously hypothesized) a primary vasculopathy. Several risk alleles and genes in proximity to SNPs identified by GWAS studies implicate Müller cell dysfunction and dysregulation of serine metabolism in pathogenesis 49,50 . We found expression patterns compatible with these hypotheses.…”
Section: Expression Of Genes Implicated In Retinal Diseasementioning
confidence: 99%
“…Mac Tel 2 is currently considered to be a primary neurodegenerative condition of the retina with secondary vascular involvement rather than (as previously hypothesized) a primary vasculopathy. Several risk alleles and genes in proximity to SNPs identified by GWAS studies implicate Müller cell dysfunction and dysregulation of serine metabolism in (49,50) pathogenesis . We found expression patterns compatible with these hypotheses.…”
Section: Inherited Vitreoretinopathies Include Familial Exudative Vitmentioning
confidence: 99%